1247 CONNECTING THROUGH CAREGIVING: PERSPECTIVE-TAKING INTERVENTIONS FOR ADULT CHILD CAREGIVERS OF PERSONS LIVING WITH DEMENTIA. (16th January 2023) - Au, A
Abstract: Introduction: With the unprecedented population growth of older adults worldwide, higher life-expectancies are creating increasingly more multigenerational interaction. Funded by the General Research Fund of the Research Grant Council in Hong Kong, the study examined the effects of perspective-taking intervention in the context of intergenerational caregiving. Method: One-hundred seventy-two adult child caregivers of persons living with Alzheimer's disease (AD) were randomised into two twelve-week interventions: 1) Connecting through Caregiving with intergenerational perspective-taking reappraisals (CTC: 91 participants) and 2) Basic Skill Building (BSB: 81participants). Both groups receive the basic skills training including 1) monitoring mood and scheduling pleasant events and 2) communication with the care recipient and 3) communication skills with other family member and helping professionals. The CTC group spends less time on basic skills and focused on perspective-taking reappraisals aiming to promote balance between self-care and caring of others. These reappraisals include: 1) connecting with self through enhancing self-awareness, 2) connecting with the care-recipient and 3) connecting with others who can help. Results: In terms of primary outcomes, as compared to the BSB group, the CTC group reported significantly greater reductions in depressive symptoms and higher levels of psychological well-being. For the secondary outcomes, the CTC group scored higher in emotional and instrumental support and also lower levels of perceived presence and reaction to behavioural and memory problems of the care recipient. Perspective-taking was found to mediate between intervention effects and reduction of depressive symptoms of the caregiver. Conclusion: The results provided evidence for the efficacy of the CTC program. With population aging, there is a rapid increase of people suffering from dementia and those who will provide caregiving. The study contributes towards enhancing sustainability of caregiving in dementia. The present findings can be relevant to countries where the demand for family caregiving is high due to collectivistic concerns.